ANALYZING OHANIANâS SOURCE CREDIBILITY MODEL ON 4 YOUTUBE MUSICIANS - Ariel Fahrezi (19014170), Muhamad
Social media is now the marketing media in the world. With the innovation of new technology and algorithm, it’s getting easy to be noticed on the internet. Everyone and everything can be famous or viral on the internet these days. One of the biggest social media platform today is YouTube and one of the biggest category on YouTube is music, and the content creator called YouTube Musicians. YouTube musicians are individuals or groups who make videos with their musical performances. They perform their own original songs, or covering other musician’s songs, making musical comedy skits, etc. Some of them is getting famous by doing this, some other still struggling to get views for their video. With this phenomenon, many other newcomers wanting to become a YouTube musician, but there are only a few knowledges to form a good strategy to produce the content. Some YouTubers come up with their own strategy to make the content, but there is still only a few of research for the content strategy. Many of these new YouTube musicians still confused whether their strategy is effective or not. So, the goal of this research is to analyze the content strategy of four YouTube musicians – two of them have more subscribers than the other two – using qualitative content analysis. The result of this research is the importance of ‘attractiveness’ in their content